The Effects Learning Management by Using 5-Steps on Learning Achievement and Retention in Learning Social Studies, Religion and Culture Department for Students in Prathomsuksa 3 - Chantharapratak, Anussara; Phatthaisong, Pornchai (Journal for Developing the Social and Community, 2023)
The purposes of this research were to 1) development of learning management by using 5-steps on learning in learning social studies, religion and culture department for students in prathomsuksa 3 to be effective to standard criteria 75/75 2) compare learning achievement in learning social studies, religion and culture department for students in prathomsuksa 3 by using 5-steps with a 75 percent criterion and 3) study on learning retention in learning social studies, religion and culture department for students in prathomsuksa 3 by using 5-steps. The target group Was 14 prathomsuksa 3 students of Nongnasang school under Roiet primary education service area office 2. The research instruments consisted of 5-step learning plan, a learning achievement test. The statistics used for data analysis were mean, percentage, standard deviation. The results of this research revealed that development of learning management by using 5-steps, The efficiency (E1/E2) is 75.58/75.95, which is equal the criteria of 75/75. compare learning achievement of students’ prathomsuksa 3 by using 5-steps, after learning by using 5-steps, accounted for 75.95 percent, which is equal to the 75 percent criteria. 3. students in prathomsuksa 3 by using 5-steps, after 2 week of learning was retention accounted for 80.95 percent.